PENGARUH HARGA MAKANAN DAN LOKASI WARUNG TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA WARMINDO RIVERSIDE - Gita Reta, Theana; Nur Hastuti , Lutfi; Putri Arumsasi, Fredina; Rahardhini, MD (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine the close relationship between the influence of food prices and stall locations on customer loyalty with customer satisfaction as a mediating variable. This research is a correlational research. The sampling technique used in this study is non-probability sampling with a sample of 42 respondents. The data collection technique is carried out using a questionnaire using a likert scale that has been tested for validity and reliability. The method in this study is a quantitative method to measure the extent of the close relationship between food prices and stall locations to customer loyalty with customer satisfaction as a mediating variable. The results of the study showed that the influence of food prices and stall locations both had a positive and significant effect on customer loyalty with the mediating variable being customer satisfaction